2008
DOI: 10.1002/jae.1028
|View full text |Cite
|
Sign up to set email alerts
|

The wages of BMI: Bayesian analysis of a skewed treatment–response model with nonparametric endogeneity

Abstract: SUMMARYWe generalize the specifications used in previous studies of the effect of body mass index (BMI) on earnings by allowing the potentially endogenous BMI variable to enter the log wage equation nonparametrically. We introduce a Bayesian posterior simulator for fitting our model that permits a nonparametric treatment of the endogenous BMI variable, flexibly accommodates skew in the BMI distribution, and whose implementation requires only Gibbs steps. Using data from the 1970 British Cohort Study, our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 29 publications
7
82
0
Order By: Relevance
“…We are unable to test whether these are problems in the current context, and can only follow the previous literature (e.g. Smith et al, 2009;Kline and Tobias 2008;Cawley, 2004) in acknowledging them as possible limitations of the instrument.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We are unable to test whether these are problems in the current context, and can only follow the previous literature (e.g. Smith et al, 2009;Kline and Tobias 2008;Cawley, 2004) in acknowledging them as possible limitations of the instrument.…”
Section: Discussionmentioning
confidence: 89%
“…We follow the previous literature (e.g. Cawley 2004; Kline and Tobias, 2008;Smith et al, 2009) and use the weight of a biological relative as an instrument for the weight of the respondent.…”
Section: Identification: Methods Of Instrumental Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work using nonparametric methods (Kline and Tobias, 2008) and quantile methods (Johar and Katayama, 2012) has shown that the effects of weight on wages varies over the distribution of wages. CDE also permits explanatory variables to have different marginal effects at different points of support of the dependent variable.…”
Section: Conditional Density Estimationmentioning
confidence: 99%
“…Shimokawa (2008) used data from China to estimate semiparametric models and fi nds that wages are lower for men and women in the tails of the BMI distribution. Kline and Tobias (2008), using data from the 1970 British Cohort study, found that marginal increases in BMI are most harmful for men who are overweight or obese and for women in the "healthy" weight range.…”
mentioning
confidence: 99%